2022
DOI: 10.1038/s41598-022-25921-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and magnetic spin structure of the antiferromagnetic triangular lattice compound LiCrTe2 investigated by $$\mu ^+$$SR, neutron and X-ray diffraction

Abstract: Two-dimensional (2D) triangular lattice antiferromagnets (2D-TLA) often manifest intriguing physical and technological properties, due to the strong interplay between lattice geometry and electronic properties. The recently synthesized 2-dimensional transition metal dichalcogenide LiCrTe$$_2$$ 2 , being a 2D-TLA, enriched the range of materials which can present such properties. In this work, muon spin rotation ($$\m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(25 reference statements)
5
3
0
Order By: Relevance
“…This negative thermal expansion observed is consistent with the recent results of synchrotron data on polycrystalline LiCrTe 2 conducted by Nocerino et al, and has been observed in other intercalated chromium tellurides [22,41]. Also a similar T N ≈ 125 K from µ + SR measurements was observed for the powder sample from Nocerino et al [41]. Considering the stoichiometric Li-content of the powder sample, the lower critical temperature derived from the µ + SR measurements could reflect the strongly dynamic character of the magnetic interactions, or the enhanced T N ≈ 148 K in the single crystals might be related to local strain effects in either sample.…”
Section: Long-range Magnetic Order In Licrte 2 Single Crystalssupporting
confidence: 92%
See 2 more Smart Citations
“…This negative thermal expansion observed is consistent with the recent results of synchrotron data on polycrystalline LiCrTe 2 conducted by Nocerino et al, and has been observed in other intercalated chromium tellurides [22,41]. Also a similar T N ≈ 125 K from µ + SR measurements was observed for the powder sample from Nocerino et al [41]. Considering the stoichiometric Li-content of the powder sample, the lower critical temperature derived from the µ + SR measurements could reflect the strongly dynamic character of the magnetic interactions, or the enhanced T N ≈ 148 K in the single crystals might be related to local strain effects in either sample.…”
Section: Long-range Magnetic Order In Licrte 2 Single Crystalssupporting
confidence: 92%
“…The neutron diffraction experiment conducted at T = 175 K (above the AFM transition, see figure 1(c)) and T = 1.8 K, see figure 2(b), show a decrease of the c axis but an increase of the a axis on lowering the temperature, indicating a shortening of the Cr-Te, Li-Te and Te-Te distances but an increase in the Cr-Cr distance, see table 1. This negative thermal expansion observed is consistent with the recent results of synchrotron data on polycrystalline LiCrTe 2 conducted by Nocerino et al, and has been observed in other intercalated chromium tellurides [22,41]. Also a similar T N ≈ 125 K from µ + SR measurements was observed for the powder sample from Nocerino et al [41].…”
Section: Long-range Magnetic Order In Licrte 2 Single Crystalssupporting
confidence: 91%
See 1 more Smart Citation
“…Another, here more likely, scenario is that a spin reorientation occurs, creating a complex magnetic structure below 65 K. The zero phase of the ZF oscillations tells us that it should be a commensurate spin structure. Consequently, this suggests that a canted AF structure is formed below T Cant ≈ 65 K, while a collinear (CL) The occurrence of canted AF orders is usually a result of competing magnetic interactions, in qualitative agreement with other systems showing a similar behavior [15,16,17,18,19,3]. No detailed structural refinement of the atomic positions in MgReO 4 is reported.…”
Section: Resultssupporting
confidence: 54%
“…20 This rare condition is responsible for the unconventional low temperature microscopic properties 21 that make NaCr 2 O 4 a fascinating study case also from a fundamental research perspective. 22 The compound crystallizes in the orthorhombic space group 62 (Pnma), in which Cr cations occupy two distinct crystallographic positions (labelled as Cr I and Cr II in Fig. 1) surrounded by octahedrally coordinated oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%